Identifying Students' Undergraduate Concept Understanding and Misconceptions on Amino Acids, Proteins, and Enzymes Using A Four-Tier Diagnostic Test - Syahmani, Syahmani; Rusmansyah, Rusmansyah; Leny, Leny; Masila, Rizqa (Journal of Mathematics Science and Computer Education, 2024)
Students' misconceptions have become common in the teaching and learning process, particularly in the challenging subject of biochemistry. This research aims to identify undergraduate students' conceptual understanding and misconceptions of amino acids, proteins, and enzymes. The research method is descriptive qualitative, and data about student conception profiles are retrieved using a four-tier diagnostic test (FTDT). The research subjects comprised 27 participants, including the Chemistry Education Study Program at Universitas Lambung Mangkurat (ULM) Banjarmasin. The sampling technique used in this study was purposive sampling. Data collection with a four-tier diagnostic test instrument consisting of 8 questions, categorizing concept understanding into understanding, not understanding the concept, and misconceptions. Data analysis was conducted by converting the results of the four-tier diagnostic test instrument into percentage data. The results showed that in the amino acids, proteins, and enzymes, of the five concepts tested, 36.67% were in the category of understanding the concept, 15.19% were in the category of not understanding the concept, and 48.15% were in the category of misconceptions. In conclusion, students' concept understanding and misconceptions are moderate. Recommended that innovative learning methods be applied to improve students' understanding of concepts in the sub-material of amino acids, proteins, and enzymes